Antioxidant activity and total phenolic content of Garcinia Prainiana stem bark / Shaari Daud … [et al.] - Daud, Shaari; Salim, Khairil Syazwan; Harun, Aiza; Ishak, Zati Ismah; Mat Hussin, Zurhana; Seman@Kamarulzaman, Ahmad Faris (Universiti Teknologi MARA, Pahang, 2022)
Finding new compounds with medicinal value from natural products is gaining popularity as they involve fewer side effects on the human body than synthetic drugs. The natural sources that provide promising antioxidants are usually phenolic compounds and triterpenoids. To date, investigations of phenolic and triterpenoid compounds from the bark of Garcinia prainiana unfortunately have not been well documented. Therefore, the bark of G. prainiana from Felda Jengka 1 Pahang was utilised in this research work. The aim is to evaluate the antioxidant potency of G. prainiana extracts through DPPH dot blot assays and radical scavenging activity. The total phenolic content (TPC) from the bark of G. prainiana was also determined using the Folin-Ciocalteu method. Crude extracts of the stem bark of G. prainiana were prepared through consecutive cold-soaking using four different types of organic solvents. The results reveal that the ethyl acetate and methanol extracts exhibited promising antioxidant activity, with IC50 values of 97.9631 μg/ml and 125.0517 μg/ml, respectively. Meanwhile, ethyl acetate extracts showed the highest TPC value of 112.2086 mg GAE/g sample. These research findings are beneficial for medicinal and pharmaceutical purposes because it provides basic scientific information that would assist in the development of drug discovery.